Polymorphisms of the 5-HT2C receptor and leptin genes are associated with antipsychotic drug-induced weight gain in Caucasian subjects with a first-episode psychosis - Templeman, Lucy A; Reynolds, Gavin P; Arranz, Belen; San, Luis (Pharmacogenetics and genomics, 2005)
Weight gain, leading to further morbidity and poor treatment adherence, is a common consequence of treatment with antipsychotic drugs. Two recent studies in the same cohort of Chinese Han subjects have shown that polymorphisms of the promoter regions of both the serotonin 5-hydroxytryptamine 2C (5-HT2C) receptor and the leptin genes, are associated with antipsychotic-induced weight gain over 10 weeks. We have investigated whether these effects remain true in a Caucasian population and following longer term treatment. Seventy-three Spanish caucasian patients with a first-episode psychosis and initially drug-naive were genotyped for the 5-HT2C receptor -759C/T and leptin -2548A/G polymorphisms. Body mass index and plasma leptin levels were monitored after 6 weeks, 3 months and 9 months of antipsychotic treatment. Patients with the -759T variant allele showed significantly less weight gain than those without this allele. This effect held true in the smaller group of patients receiving olanzapine. The -2548 leptin polymorphism was not associated with short-term (6 week and 3 month) weight increases but did show significant association with 9-month antipsychotic-induced weight gain. The 5-HT2C -759 genotype was significantly associated with pre-treatment plasma leptin levels. These findings confirm the importance of two genetic factors associated with long-term antipsychotic-induced weight increases in schizophrenia, and implicate a role for leptin in the 5-HT receptor-mediated weight regulation.